Two-Step Method for Instability Damage Detection in Tower Body of Transmission Structures. Issue 1 (January 2013) - Qu, Weilian; Song, Wanjun; Xia, Yong; Xu, Youlin; Qin, Wenke; Jiang, Zhicai
Instability damage may occur in some members of the transmission tower subjected to the downburst, and eventually the damage accumulation may further lead to the failure of the tower. Therefore, it is extremely essential to identify and repair the damaged major vertical members in tower body timely. The relationship surface of instable member among axial compression force, bending moment at the end and axial stiffness is determined. The results show that the axial stiffness of the instability members reduces to zero gradually. Accordingly, a two-step detection method of the major vertical member instability damage is presented. The first step detection is used to find the possible buckling damaged regions by using wavelet packet energy curvature change rate index. The second step is used to identify location of buckling damaged major member that appears in the possible damaged subregions based on the theory of modal strain energy and interval estimation. Finally, the proposed method is applied to a realistic transmission tower and experimental verified with a steel tube tower. The results indicate that the two-step detection method is effective and feasible.